The returns to private education: Evidence from Mexico - Chiara Binelli; Marta Rubio-Codina (Institute for Fiscal Studies (IFS), 2012)
Despite the rapid expansion and increasing importance of private education in developing countries, very little is known about the impact of studying in private schools on educational attainment and wages. This paper contributes to filling this gap by estimating the returns to private high schools in Mexico. We construct a unique dataset that combines labor market outcomes and historical school census data, and we exploit changes in the availability and size of public and private high schools across states and over time for identification. We find substantial evidence of a positive effect of studying in a private high school on wages after college graduation, and we discuss alternative mechanisms that can explain this finding.
Keywords: J31; J24; C36; 330; Private and Public Schools; Returns to Education; Mexico